La lingua è una questione di potere: linguaggio giuridico e lingua di genere - Cavagnoli, Stefania (Linguistik Online, 2024)
The contribution deals with the relationship between language, legal language and power. It is not possible to think about language outside of a cultural context; culture primes the language used in common and specialized spheres, handing down linguistic traditions and routines.Especially when considering the Italian language such traditions and routines are androcentric. The point of reference, the linguistic ego is always thought of as masculine, while the feminine is considered a normative gap. In light of this, we consider a number of legislative documents, aimed at and designed to respect gender-appropriate usage, in the Italian context.For the European sphere, however, an example is proposed from the contrastive study of European directives and their transposition for five different languages (Italian, English, German, French and Spanish).